1998
DOI: 10.1248/bpb.21.535
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid Assay of Granisetron in Biological Fluids from Cancer Patients.

Abstract: A convenient high-performance liquid chromatography (HPLC) was developed for the rapid assay of granisetron (GRN) in biological fluids, such as serum, urine, and pleural effusion, from cancer patients. Extrelut-1 was used for the solid-phase extraction. HPLC was carried out using a LiChroCART cartridge column packed with Lichrospher 100 CN and a mobile phase consisting of 0.1 M acetate buffer (pH 3.5) and acetonitrile (7:3). A fluorescence detector of 290 nm for excitation and 365 nm for emission was used. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 0 publications
2
10
0
Order By: Relevance
“…The bedridden elderly patients in this study were in the terminal stage of lung cancer, and it was, therefore, probable that they had extracellular fluids like thoracic effusion and edema as the third space for the distribution of GRN. In a recent paper, 7) we reported that intravenously administered GRN was rapidly and highly distributed throughout the pleural effusion and then disappeared from the pleural effusion in a two-compartment model. It might be assumed that an elimination route of GRN, which distributed into the third space, is back-diffusion into the blood-stream.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…The bedridden elderly patients in this study were in the terminal stage of lung cancer, and it was, therefore, probable that they had extracellular fluids like thoracic effusion and edema as the third space for the distribution of GRN. In a recent paper, 7) we reported that intravenously administered GRN was rapidly and highly distributed throughout the pleural effusion and then disappeared from the pleural effusion in a two-compartment model. It might be assumed that an elimination route of GRN, which distributed into the third space, is back-diffusion into the blood-stream.…”
Section: Resultsmentioning
confidence: 95%
“…The HPLC system used was a Shimadzu LC-10A (Kyoto, Japan) equipped with a Shimadzu RF-10A fluorescence detector and Shimadzu CTO-10A column oven. Chromatographic condition were as follows: 7) column, LiChroCART ® packed with LiChrospher 100CN (CicaMerck, 250ϫ4 mm i.d., 5 mm); mobile phase, 0.1 M acetate buffer (pH 3.5)-acetonitrile (7 : 3); flow rate, 1 ml/min; column temperature, 40°C; detector, 290 nm for excitation and 365 nm for emission.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 A review of the literature revealed no methods for determination of granisetron in pharmaceutical dosage forms and dissolution medium and previously reported methods were mainly focused on the analysis of this drug in biological fluids. Previous studies have reported HPLC methods with fluorescence detection [5][6][7][8] and LC-MS/MS methods 9,10 for determination of granisetron in human biological fluids. According to the International Conference on Harmonization (ICH) guidelines 11 and USP, 3 the assay method for determination of an active substance should be stability indicating to evaluate the drug in the presence of its degradation products.…”
Section: Introductionmentioning
confidence: 99%
“…H and 13 C NMR and 2D NMR spectral data. The HPLC chromatographic conditions were chosen to achieve satisfactory resolution between the impurities and API with shortest analysis time.…”
mentioning
confidence: 99%